Particle Size Analysis of Barium Titanate Powder by Slow-Rate Sol-Gel Process Route - Balachandran, R; Yow, HK; Jayachandran, M; Yusof, Wan Yusmawati Wan; Saaminathan, V (2006)
In this research work, different compositional ratios of Barium Titanate [BT] powders have been prepared using slow-rate gellification by sol-gel route. The as-prepared materials have been calcinated at 300 degrees C for 8 hours to remove the presence of carbon, and subsequently annealed at 700 degrees C for one hour for the phase formation. After annealing, the finely grinded powders were characterized by X-Ray diffractometer [XRD], Atomic Force Microscope [AFM] and Nano particle size analyzer [NPSA]. The XRD pattern shows that the material was BT with polycrystalline phase. It exhibited tetragonal phase with crystalline size in the range of 97 nm. The lattice constants 'a' and 'c' were perfectly matched with the standard reports. The surface morphology study by AFM shows that the materials were homogenously fine grains. The average particle sizes reduce from 750 urn to 78.49 nm when the concentration of barium salt decreases. This observation clearly indicates that the tuning of the particle sizes is possible by controlling the compositional ratios of barium and titanium. The particle distributions of the samples have also been analyzed by nano particle size analyzer. In this work, samples with equal amount of barium and titanium exhibited particle size distribution down to 100 urn range, with good structural and morphological properties.